PROPOSED KNOWLEDGE MANAGEMENT SYSTEM FOR DAILY WORKERS : CASE OF FOOD AND BEVERAGE DEPARTMENT CY HOTEL BANDUNG (The Indonesian Journal of Business Administration, 2021)
Knowledge is an essential company aid that offers sustainable aggressive gain. For an company, expertise is an essential strategic asset to attain and keep its aggressive gain in comparison with competitors Like the CY Hotel Bandung, the Human Resources Department employs many daily workers to help the CY Hotel Bandung project. Nevertheless, the human resources department of the daily workers at the CY Hotel Bandung lacks knowledge and experience related to daily work. This situation makes them very dependent on their superiors to assist them in completing their work. But in reality, not everyone wants and has time to share their knowledge in every situation. Therefore, Human Resources Department of CY Hotel Bandung needs a comprehensive knowledge management system to support the occurrence of an effective knowledge sharing among the organization and daily workers to improve the organization's work environment and effectiveness at work.Activities will begin in a series of activities carried out based on the five stages of the knowledge management implementation process for the implementation plan. The knowledge management objectives and approaches are identified to adjust the knowledge management system according to the current situation and problems faced by the company to support business processes so that the knowledge management system can work efficiently and effectively.The implementation plan has the concern to improve practice of knowledge management. Proposed important activity that can maximize the full potential of knowledge management and innovation in the company. The implementation activity will consist of 23 (twenty-three) activities to be fulfilled with the proposed timeframe for 3 months. The resources needed are the management, managers, daily workers, and IT which will go through processes such as forum discussion, brainstorming, and lesson learned among other things.Keywords: Knowledge Management, Daily Workers, People, Process & Technology, Knowledge Management System, Low Touch Economy